Investigation of the tensile response and the microstructural evolution during hot drawing of multi-layered, ultrafine-grained AA6014 sheets by thermomechanical analyzes - Zettl, Bastian; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2022)
Mechanical strengthening of sheet material can be realized by accumulative roll bonding, which belongs to the severe plastic deformation processes. Beside fine-grain hardening also work and precipitation hardening is responsible for the rise of material strength. However, this is also accompanied by a significant decrease in ductility. Thus, the need for an enhancement of ductility is essential for a sufficient formability in later applications and was already introduced by tailored heat treatments. The challenge, however, is to realize a process temperature that leads to a degradation of dislocations and dissolution of MgSi-precipitations, without a recrystallization of the fine-grained microstructure to coarse grain sizes. In order to identify a suitable temperature range to avoid recrystallization, hot forming experiments are carried out at successive temperatures from 20 to 300 °C. Tensile specimens are drawn with the thermomechanical simulator Gleeble 3500 (Dynamic Systems Inc.) aided by the strain measurement system Aramis (GOM GmbH). The aim is to investigate the dependence of the mechanical properties from the forming temperature in order to identify a temperature range, in which high strength with simultaneous enhanced ductility is maintaine